The Effect of Grain Size on the Mechanical and Optical Properties of Spark Plasma Sintering‐Processed Magnesium Aluminate Spinel MgAl2O4. Issue 1 (11th October 2012) - Rothman, Amnon; Kalabukhov, Sergey; Sverdlov, Nataliya; Dariel, Moshe P.; Frage, Nahum
<x xml:space="preserve">Abstract</x> The study deals with the effect of the SPS parameters and LiF doping on the mechanical and optical properties polycrystalline magnesium aluminate spinel (PMAS) with emphasis on the grain size of the final product. Sintering at 1300°C of undoped powder yielded fully dense submicrometer (0.4–0.6 μm) samples with elevated mechanical properties (1600HV and 300MPa bending strength). Doped samples had a larger, 40 μm grain size, lower, 1450HV, hardness and 150MPa bending strength. The transmittance of the doped samples (80% at 500 nm wavelength) was higher than that of the undoped ones. Thus, the required functionality of the ceramic dictates the choice of parameters for the fabrication of dense transparent PMAS.